knowledge-based Nursing in Frontotemporal Dementia: A Scoping Review - Eid, Hege Rasmussen (Nordisk Tidsskrift for Helseforskning, 2023)
Background: Frontotemporal dementia (FTD) often affects younger persons and has a complex symptom picture. Nursing care for patients with FTD is challenging, yet the experience- and research-based knowledge about this is scarce. Purpose: To examine the existing international research-based knowledge, Norwegian national guidelines and professional advice about nursing care for patients with FTD. Method: Scoping Review. Results: 19 articles were included. International research literature shows that cooperation with family caregivers, competence in nurses, individually adapted environments and activities and treatment interventions should be part of nursing care for patients with FTD. Norwegian national guidelines do not describe nursing care for patients with FTD. Conclusion: The complexity of FTD poses other demands in nursing than other dementia diseases. Norwegian national guidelines for dementia in general reflect some of the recommendations found in the international research literature, but more diagnose-specific guidelines for FTD may be needed. This should be examined further in future studies.